Benefits and pitfalls of learning anatomy using the dissection module in an indian medical school: A millennial Learner's perspective - Sneha Guruprasad Kalthur; Arvind Kumar Pandey; Sushma Prabhath (Elsevier, 2022)
Background: For generations, the use of cadavers has been the chief pillar for learning anatomy. However, the limited availability of cadavers and the advent of modern technologies in learning have led to the use of substitutes such as prosection, anatomical models, and audio-visual (AV) aids. The current study was therefore undertaken to seek students' opinions regarding the usefulness of the traditional dissection module in the modern era of teaching-learning. Methodology: The questionnaire-based study involved 145 medical undergraduate students exposed to dissection in anatomy during their first year (2018-19). Three themes were identified based on the students' responses. They were advantages of learning anatomy by dissection, disadvantages of learning anatomy by dissection, and dissection classes versus other educational resources used in learning anatomy. The students' opinions related to the themes were considered. Results: The majority of the students stated that the act of dissection deepens one's understanding (91.8%) and provides a three-dimensional perspective of structures (92.4%). A group of students felt that the dissection is time-consuming (57%) and prosection (64.6%) helped them gain information quicker. However, when asked whether dissection should be eliminated from the curriculum, the majority (86%) of the students disagreed. However, the students agreed that dissection should be supported by educational tools (74%). Conclusion: The study strengthens the belief of using dissection for better anatomy learning and adds that dissection hall teaching is the best approach for anatomy teaching-learning. Millennial learners prefer the act of dissection to learn practical anatomy and consider the recent advances such as simulator-based education, video demonstrations, virtual and augmented reality only as supplements.